Konsep Pendidikan Islam dalam Surat Luqman Ayat 12-19 Sebagai Relevansi Penguatan Kesehatan Mental Generasi Z (Berdasarkan Tafisr Al-Azhar Karya Hamka) - Hambali, M Wahid; Islah, Islah (CV. Rayyan Dwi Bharata, 2025)
This research discusses the concept of Islamic education in Surah Luqman verses 12-19 based on the Al-Azhar commentary by Hamka and its relevance to strengthening the mental health of Generation Z. These verses cover three main aspects of education: belief (verses 12, 13, 16), sharia (verses 14, 15, 17), and morals (verses 14, 15, 18, 19). Luqman's messages to his son through dialog emphasize the importance of direct communication in education. Generation Z, born in the digital era, has unique characteristics that include familiarity with technology, concern for global issues, and the need for strengthening mental health. Good mental health involves harmony of psychiatric functions, self-acceptance, and positive relationships with God and others. In this context, Islamic education, which emphasizes tawhid, gratitude, worship, and harmonious relationships with parents and society, provides a strong foundation for building resilient mental health. The integration of Islamic education values from Surah Luqman verses 12-19 into the lives of generation Z has the potential to create individuals who are spiritually, emotionally and socially healthy. This can be achieved through Islamic counseling, which helps individuals understand religious values, accept themselves, and develop positive life habits.